Building digital twins of 3D printing machines. (1st July 2017) - DebRoy, T.; Zhang, W.; Turner, J.; Babu, S.S.
Abstract: Geometrical conformity, microstructure and properties of additively manufactured (AM) components are affected by the desired geometry and many process variables within given machines. Building structurally sound parts with good mechanical properties by trial and error is time-consuming and expensive. Today's computationally-efficient, high-fidelity models can simulate the most important factors that affect the AM products' properties, and upon validation can serve as components of digital twins of 3D printing machines. Here we provide a perspective of the current status and research needs for the main building blocks of a first generation digital twin of AM from the viewpoints of researchers from several organizations. Graphical abstract: